Price bubbles in lithium markets around the world - Restrepo, Natalia; Uribe, Jorge M.; Guillen, Montserrat (Frontiers in Energy Research, 2023)
The global energy transition to low-carbon technologies for transportation is heavily dependent on lithium. By leveraging advances in time-series econometrics we show that lithium prices (carbonate and hydroxide) have recently experienced market explosive behaviors, particularly from 2016 to mid-2018, and in most lithium markets also from October 2021 to December 2022, thus, the global lithium markets are currently experiencing explosive dynamics. These explosive episodes are accompanied by market corrections and extreme uncertainty which, in the case of lithium, may put at risk the future continuous supply needed for manufacturing lithium-based batteries for the electric vehicle. Governments and private stakeholders could reduce uncertainty imposed by these unpredictable dynamics, for instance, by establishing public stabilization funds and setting up capital buffers that help to diversify operational and market risks induced by future price reversals. Such funds should be ideally located in portfolios, such as the global stock markets or other energy commodities, which exhibit idiosyncratic explosive dynamics unsynchronized with the episodes observed in lithium markets.